2015
DOI: 10.1016/j.tem.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Biliverdin reductase isozymes in metabolism

Abstract: Biliverdin reductase (BVR) isozymes, BVRA and BVRB, are cell surface membrane receptors with pleiotropic functions. This review compares, for the first time, the structural and functional differences of the isozymes. They reduce biliverdin, a byproduct of heme catabolism, to bilirubin, display kinase activity and BVRA, but not BVRB, can act as a transcription factor. The binding motifs present in the BVR isozymes allow for a wide range of interactions with components of metabolically important signaling pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 77 publications
2
112
1
Order By: Relevance
“…Bilirubin increased tolerance to islet allograft by both its anti-inflammatory and anti-oxidative properties 62,63 . Additionally, biliverdin reductase acts as transcriptional factor and increases HO-1/HO-2 levels and HO activity 26 and protects against glucose intolerance (reviewed in 64 ) through a mechanism involving activation of phosphatidylinositol 3-kinase (P13K) 65 . Unconjugated bilirubin mediated HO-1-induced vascular benefit in diabetes 66 and administration of mesobiliverdin analogues of biliverdin to the pancreas lowered blood glucose and increased insulin function 67 .…”
Section: Biological Action Of Bilirubin/biliverdinmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilirubin increased tolerance to islet allograft by both its anti-inflammatory and anti-oxidative properties 62,63 . Additionally, biliverdin reductase acts as transcriptional factor and increases HO-1/HO-2 levels and HO activity 26 and protects against glucose intolerance (reviewed in 64 ) through a mechanism involving activation of phosphatidylinositol 3-kinase (P13K) 65 . Unconjugated bilirubin mediated HO-1-induced vascular benefit in diabetes 66 and administration of mesobiliverdin analogues of biliverdin to the pancreas lowered blood glucose and increased insulin function 67 .…”
Section: Biological Action Of Bilirubin/biliverdinmentioning
confidence: 99%
“…Additional studies have demonstrated that both free and albumin-bound bilirubin can inhibit the oxidation of low density lipoproteins (LDL) 73 . The roles of bilirubin and biliverdin reductase in obesity and CVD have been recently reviewed 64,72 .…”
Section: Biological Action Of Bilirubin/biliverdinmentioning
confidence: 99%
“…Another interesting protein significantly increased in abundance is BLVRB, a flavin reductase, which converts biliverdin IXβ to bilirubin Ixβ and the latter in turn increases insulin sensitivity (O’Brien et al, 2015) as probable defense mechanisms against the ensuing insulin resistance. The increase in the BLBVRB protein in the MUHO group has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Heme oxygenase (HO) is a critical component of a major antioxidant pathway by the generation of bilirubin (1, 12). Initially, HO breaks down heme to biliverdin, free iron, and carbon monoxide (CO), and biliverdin is then reduced to bilirubin by the enzyme biliverdin reductase (BVR) (1, 12).…”
Section: Introduction and Methods Principlementioning
confidence: 99%
“…Initially, HO breaks down heme to biliverdin, free iron, and carbon monoxide (CO), and biliverdin is then reduced to bilirubin by the enzyme biliverdin reductase (BVR) (1, 12). In adults, this reaction is catalyzed by the A isoform of BVR (BVRA).…”
Section: Introduction and Methods Principlementioning
confidence: 99%